The Clean And Healthy Life Education Socialization For Students At Kuprik Inpres Elementary School - Umiyati Haris; Muhammad Novan Prasetya; Najdah Thalib; Parman Jasnur; Hubertus Oja; Andri Irawan; Nur Jalal; Everitus Rikardus (Jurnal Pengabdian Masyarakat Indonesia Sejahtera, 2023)
This community service aims to increase students' awareness and understanding of the importance of clean and healthy life education (PHBS) at Inpres Kuprik Elementary School. PHBS is a concept that involves various healthy habits, such as washing hands, maintaining personal hygiene, and maintaining a clean environment. This service aims to provide socialization to students about PHBS and teach them practical steps to apply it in everyday life. The method used in this service is the delivery of PHBS material through lectures, group discussions, and direct practical activities. Students will be given an understanding of the importance of PHBS and the positive impact they will get if they adopt clean and healthy living habits. The expected results of this service are an increase in students' knowledge about PHBS and a change in behavior that leads to clean and healthy living habits. With this socialization, it is hoped that students will become agents of change who can influence their peers and the community around them to adopt clean and healthy living habits. In addition, this dedication is also expected to increase the participation of educators and parents of students in building a PHBS culture in schools and the surrounding environment. In conclusion, after this service has been done, students of Kuprik Elementary School are having understanding dan implementing the importance of PHBS in daily life.